2021
DOI: 10.1021/acs.analchem.0c04680
|View full text |Cite
|
Sign up to set email alerts
|

Method for Molecular Layer Deposition Using Gas Cluster Ion Beam Sputtering with Example Application In Situ Matrix-Enhanced Secondary Ion Mass Spectrometry

Abstract: We introduce a technique for the directed transfer of molecules from an adjacent reservoir onto a sample surface inside the vacuum chamber of a ToF-SIMS instrument using gas cluster ion beam (GCIB) sputtering. An example application for in situ matrix-enhanced secondary ion mass spectrometry (ME SIMS) is provided. This protocol has attractive features since most modern SIMS instruments are equipped with a GCIB gun. No solvents are required that would delocalize analytes at the surface, and the transfer of matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…23,24 The most recent developments in ME-SIMS involve the in-situ transfer of matrices such as DHB and CHCA using a gas cluster ion beam, making them compatible with three-dimensional imaging. 25,26 These matrices constitute a partial molecular structure of benzene, in which the conjugated double bonds can absorb ultraviolet light from the MALDI laser probe. 27 Furthermore, protonated matrix molecules are important chemical species for analyte ionization in MALDI measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The most recent developments in ME-SIMS involve the in-situ transfer of matrices such as DHB and CHCA using a gas cluster ion beam, making them compatible with three-dimensional imaging. 25,26 These matrices constitute a partial molecular structure of benzene, in which the conjugated double bonds can absorb ultraviolet light from the MALDI laser probe. 27 Furthermore, protonated matrix molecules are important chemical species for analyte ionization in MALDI measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ionic liquids such as 1‐methylimidazolium CHCA, tripropylammonium CHCA, and graphene oxide, which have been used as MALDI matrices, are similarly effective for TOF‐SIMS measurements 23,24 . The most recent developments in ME‐SIMS involve the in‐situ transfer of matrices such as DHB and CHCA using a gas cluster ion beam, making them compatible with three‐dimensional imaging 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lorenz et al showed that large argon clusters could be used to transfer an organic material from one surface onto another with a reduced fragmentation. 31,32 This transfer of intact molecule was extended by our group to larger proteins to develop a softlanding technique in situ a ToF-SIMS instrument. Lysozyme, a protein of 14 kDa, was successfully landed on a silicon wafer with retention of its activity, as was verified afterward via a bioassay in solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One drawback is that direct patterning with the beam is impossible (the deposition pattern mirrors the angular distribution of sputtered molecules), but on the other hand, much larger fluxes can be attained than by selecting only charged molecules. Beside lysozyme, a range of MALDI matrices , and kilodalton molecules including polystyrene oligomers, Irganox 1010, angiotensin, and insulin could also be transferred undamaged. The fraction of intact molecules was inversely proportional to the energy per atom ( E / n ) of the impinging cluster ions. Though this variant of soft landing appears to be a promising new technique for building up complex molecular or hybrid multilayers on virtually any substrate material, a number of fundamental questions still remain open.…”
Section: Introductionmentioning
confidence: 99%